2010
DOI: 10.1200/jco.2009.24.5480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Tobacco Smoke on the Incidence of Mutations in Epidermal Growth Factor Receptor Gene in Never-Smoker Patients With Non–Small-Cell Lung Cancer

Abstract: ETS exposure is negatively associated with EGFR mutations in never smokers with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
5
49
0
4
Order By: Relevance
“…17,18 All of our patients with EGFR mutation (n= 3) had adenocarcinoma in parallel to the literature and two of them had no smoking history. 16,17,19,20 It was reported that passive smoking ('environmental tobacco smoke exposure') might have been inversely related to EGFR mutations, even in the people who had never smoked actively. 20 It was not easy to document 'real' passive smokers among non-smokers in our study since the criteria for second-hand smoke 'intensity' are not so clear almost in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 All of our patients with EGFR mutation (n= 3) had adenocarcinoma in parallel to the literature and two of them had no smoking history. 16,17,19,20 It was reported that passive smoking ('environmental tobacco smoke exposure') might have been inversely related to EGFR mutations, even in the people who had never smoked actively. 20 It was not easy to document 'real' passive smokers among non-smokers in our study since the criteria for second-hand smoke 'intensity' are not so clear almost in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,19,20 It was reported that passive smoking ('environmental tobacco smoke exposure') might have been inversely related to EGFR mutations, even in the people who had never smoked actively. 20 It was not easy to document 'real' passive smokers among non-smokers in our study since the criteria for second-hand smoke 'intensity' are not so clear almost in the literature. So, its effect on EGFR mutation rates could not have been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, approximately 25% of lung cancers occur in lifelong never-smokers, and the proportion of neversmokers with lung cancer has been increasing over time. [1][2][3][4] The development of lung cancer in never-smokers (LCINS) is of great concern in East Asian countries, and some estimates suggest that up to 70% of these cancers in women may be unrelated to tobacco smoking. 1,[5][6][7] Currently, LCINS is regarded as a distinct disease entity with a unique tumorigenic pattern, clinicopathologic features, and natural history.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR mutations have been reported in approximately 50% of never-smoker lung cancer patients compared with 10% of smoker lung cancer patients. 2,[12][13][14] The high frequency of EGFR mutations in never-smoker patients is associated with dramatic and durable responses to EGFR tyrosine kinase inhibitors (TKIs). 2,[15][16][17][18][19][20] ALK rearrangement, which results from a small inversion within chromosome 2p, is a newly identified driver oncogene in nonsmall cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation